Inequities in paid parental leave across industry and occupational class: Drivers and simulated policy remedies - Holly Elser; Connor Williams; William H. Dow; Julia M. Goodman (Elsevier, 2022)
Introduction: Paid family leave (PFL) has the potential to reduce persistent health disparities. This study aims to characterize differences in access to paid leave by industry sector and occupational class. Methods: The Bay Area Parental Leave Survey of Mothers included respondents 18 years of age or older who worked in the San Francisco Bay Area and gave birth from 2016 to 2017. Using linear probability models, we examined differences in five separate measures of PFL by industry sector and occupational class. We extended our regression analysis to simulate the full pay equivalent (FPE) weeks of leave that would have been taken under hypothetical scenarios of increased uptake and wage replacement rates. Results: Our study included 806 women in private for-profit or non-profit jobs. In fully adjusted models, blue-collar workers were 10.9% less likely to take 12 weeks of paid parental leave versus white-collar workers (95% CI: -25.9, 4.1). Respondents were 19.2% less likely receive 100% of their regular pay if they worked in education and health services (−29.1, −9.3) and 17.0% less likely if they worked in leisure and hospitality (−29.5, −4.4) versus respondents in professional and financial services. Respondents in leisure and hospitality reported 1.6 fewer FPE weeks of leave versus respondents in professional and financial services (−2.73, −0.42) and blue-collar respondents reported an average of 1.5 fewer FPE weeks versus white-collar workers (−2.66, −0.42). In our simulation analysis, when we manipulated rates of uptake for paid leave, the disparities in FPE by industry sector and occupational class were eliminated. Conclusion: We observed substantial inequities in access to paid leave by industry sector and occupational class. These findings underscore the potential importance of universal PFL programs with universal benefits to reduce clear inequities that persist within the labor market today.